2007
DOI: 10.1111/j.1574-6968.2006.00547.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of triclosan onSalmonella typhimuriumat different growth stages and in biofilms

Abstract: Triclosan is a potent biocide that is included in a diverse range of products. This research was aimed to investigate the susceptibility of planktonic and biofilm-associated Salmonella enterica serovar Typhimurium to triclosan, and to identify potential mechanisms of adaptation. The effect of triclosan was studied on planktonic Salmonella (log and stationary phases), on biofilm-associated cells, on bacteria derived from disrupted biofilms and on a biofilm-deficient mutant. An eight-log reduction of exponential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
63
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(70 citation statements)
references
References 42 publications
7
63
0
Order By: Relevance
“…The impact of drug exporters on biofilm formation varies in different species, so P. aeruginosa mutants deficient in or overproducing RND pumps can still form biofilms (16,884), while the loss or inhibition of any of 9 MDR pumps (AcrAB, AcrD, AcrEF, MdtABC, MdsABC, EmrAB, MdfA, MdtK, and MacAB) or the TolC OM protein in Salmonella impairs biofilm formation with reduced production of curli (885,886). Interestingly, the biocide triclosan induces acrAB and marA expression in Salmonella biofilm cells (887). Similarly, E. coli mutants with a genetic deletion of one of the RND (acrAB, acrD, acrEF, mdtABC, and mdtEF), MFS (emrAB, emrD, and emrKY), SMR (emrE), and ABC (macAB) pump genes resulted in reduced biofilm formation (888).…”
Section: Role Of Efflux Pumps In Biofilm Formation and Resistancementioning
confidence: 99%
“…The impact of drug exporters on biofilm formation varies in different species, so P. aeruginosa mutants deficient in or overproducing RND pumps can still form biofilms (16,884), while the loss or inhibition of any of 9 MDR pumps (AcrAB, AcrD, AcrEF, MdtABC, MdsABC, EmrAB, MdfA, MdtK, and MacAB) or the TolC OM protein in Salmonella impairs biofilm formation with reduced production of curli (885,886). Interestingly, the biocide triclosan induces acrAB and marA expression in Salmonella biofilm cells (887). Similarly, E. coli mutants with a genetic deletion of one of the RND (acrAB, acrD, acrEF, mdtABC, and mdtEF), MFS (emrAB, emrD, and emrKY), SMR (emrE), and ABC (macAB) pump genes resulted in reduced biofilm formation (888).…”
Section: Role Of Efflux Pumps In Biofilm Formation and Resistancementioning
confidence: 99%
“…Subinhibitory concentrations of the aminoglycoside antibiotic tobramycin has been shown to induce biofilm formation in P. aeruginosa (135). Another antimicrobial compound, triclosan, enhances transcription of cellulose synthesis genes in S. Typhimurium (310). Because cellulose is part of the biofilm matrix of S. Typhimurium, triclosan may activate biofilm formation in this organism.…”
Section: Regulationmentioning
confidence: 99%
“…Triclosan also caused upregulated the transcription of other genes (e.g. micF, acrAB, marA bcsA, bcsE) in Salmonella that might help induce further resistance [16]. Schweizer [17] reported that some bacterial strains (such as gram-negative bacteria) use a multiple triclosan resistance mechanism, including active efflux from cell where bacteria actively pump TCS out of the cell [18].…”
Section: Triclosan -Mode Of Actionmentioning
confidence: 99%